Preparation of high-strength and high-toughness natural polymer-based hydrogel wound dressing with excellent photo-thermal performance

A high-strength and high-toughness natural polymer hydrogel was prepared through a cross-linked network structure based on sodium alginate, chitosan and hyaluronic acid, combined with cuttlefish nanoparticles. This solved the problems of poor photothermal performance, insufficient strength and toughness, and weak antioxidant capacity of existing hydrogels, achieved excellent photothermal performance and biocompatibility, and is suitable for wound healing.

CN120617607APending Publication Date: 2025-09-12QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510862521.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-25
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

Existing hydrogel dressings have problems such as poor photothermal performance, insufficient strength and toughness, weak antioxidant capacity, and most of them contain biological toxicity.

Method used

Using sodium alginate, chitosan and hyaluronic acid as the basis, by loading cuttlefish nanoparticles to form a cross-linked network structure, combined with polyvinyl alcohol and polyvinyl pyrrolidone, a high-strength and high-toughness natural polymer hydrogel with excellent photothermal properties was prepared. The synergistic effect of dopamine and cuttlefish nanoparticles was used to improve the antioxidant and antibacterial properties.

Benefits of technology

The prepared hydrogel dressing can be heated to 60°C under 808 laser irradiation. It has excellent mechanical strength, antioxidant and antibacterial properties, good biocompatibility, is suitable for wound healing, and does not harm skin tissue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120617607A_ABST
    Figure CN120617607A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of multifunctional wound dressings, and provides preparation of a high-strength and high-toughness natural polymer hydrogel wound dressing with excellent photo-thermal performance. The preparation method comprises the following steps: firstly, separating cuttlefish element nanoparticles from ink sacs of cuttlefishes, then oxidizing sodium alginate by sodium periodate to generate oxidized sodium alginate with aldehyde groups, and grafting dopamine onto the oxidized sodium alginate at the same time; the preparation method comprises the following steps: preparing a polydopamine-oxidized sodium alginate network, polymerizing polyvinyl alcohol and polyvinylpyrrolidone, adding the polydopamine-oxidized sodium alginate network while polymerizing polyvinyl alcohol and polyvinylpyrrolidone, and finally doping cuttlefish element nanoparticles into the polymer network to obtain the natural polymer-based multifunctional hydrogel wound dressing wrapping the cuttlefish element nanoparticles. The dressing disclosed by the invention is prepared from all-natural high polymer materials, is environment-friendly and excellent in biocompatibility, and can perfectly accord with the physiological characteristics of human skin; in addition, the hydrogel also has good photo-thermal performance, oxidation resistance, strength and toughness, and can effectively inhibit the growth of bacteria at the wound to ensure that the hydrogel is not damaged during wound healing and does not cause damage to skin tissues.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of multifunctional wound dressings and relates to the preparation of a high-strength and high-toughness natural polymer-based hydrogel wound dressing with excellent photothermal properties. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.

[0003] Hydrogel wound dressings have shown wide application potential in clinical treatment in recent years due to their unique physicochemical properties and biocompatibility.

[0004] However, the hydrogels currently prepared still have many problems. First, most hydrogel dressings do not have good photothermal properties and achieve long-term antibacterial effects by integrating metal nanoparticles, and they have high biological toxicity. Second, the strength and toughness of current hydrogels are low, making them prone to breakage. Third, the antioxidant capacity of existing hydrogels is weak, resulting in a high content of reactive oxygen species that hinders wound healing.

[0005] Therefore, there is an urgent need to develop a high-strength and high-toughness natural polymer-based hydrogel wound dressing with excellent photothermal properties. Summary of the Invention

[0006] In order to solve the above problems, the present invention provides a preparation method for a high-strength and high-toughness natural polymer-based hydrogel wound dressing with excellent photothermal properties.

[0007] The present invention prepares the target hydrogel through the following design ideas: Sodium alginate is selected as one of the hydrogel materials because it has lower cost and milder and more controllable gel formation conditions compared to chitosan and hyaluronic acid. In addition, because polysaccharides are rich in carboxyl, hydroxyl, and amino functional groups on their polymer chains, they can be modified to enhance mechanical properties and improve antioxidant properties. Polyvinyl pyrrolidone-based hydrogels are biocompatible, non-toxic, chemically inert, and pH-stable. Polymerization with polyvinyl alcohol and sodium alginate can further enhance the mechanical properties of the hydrogel. Polyvinyl pyrrolidone has a structure similar to that of proteins and tissue fluid, which makes it biologically relevant. Finally, cuttlefish nanoparticles are loaded into the hydrogel to impart excellent photothermal properties. Since the difference in the photothermal performance of the hydrogel is only related to the amount of cuttlefish nanoparticles loaded, the method of introducing the cuttlefish nanoparticles has no effect on the photothermal performance. However, different introduction methods are only optimizations of the hydrogel system synthesis process. OSA-cuttlefish@PDA is connected through EDC / NHS activation reaction, with a low grafting rate and a complicated experimental process. OSA-PDA is carried out through self-initiated Schiff base, with a simple experimental process and can form a separate Schiff base network. Cuttlefish is also incorporated into the PDA network.

[0008] The present invention provides a preparation method for a high-strength and high-toughness natural polymer hydrogel wound dressing with excellent photothermal properties. This method solves the problems of existing hydrogels, such as poor strength and toughness, easy breakage, poor photothermal properties, and weak antioxidant capacity.

[0009] The invention first uses sodium periodate to oxidize sodium alginate to produce oxidized sodium alginate with aldehyde groups. Then, cuttlefish pigment nanoparticles are separated from cuttlefish ink sacs using centrifugation. Finally, the separated cuttlefish pigment nanoparticles are added to a mixed solution of polyvinyl alcohol, polyvinyl pyrrolidone, oxidized sodium alginate, and polydopamine to form a multifunctional polymer hydrogel wound dressing with antibacterial, anti-inflammatory, and antioxidant properties, excellent photothermal properties, and high adhesion. The hydrogel is made from environmentally friendly, environmentally friendly, and highly biocompatible raw materials, and is harmless to human skin.

[0010] In order to achieve the above object, the present invention adopts the following technical solutions:

[0011] The first aspect of the present invention provides a method for preparing a high-strength and high-toughness natural polymer hydrogel wound dressing with excellent photothermal properties, comprising:

[0012] The polyvinyl alcohol solution and polyvinyl pyrrolidone are mixed uniformly to obtain a PVA-PVP solution;

[0013] The oxidized sodium alginate and dopamine are mixed uniformly in a solution to obtain an OSA-PDA solution;

[0014] The OSA-PDA solution is added to the PVA-PVP solution to obtain a mixed solution of PVA-PVP-OSA-PDA, and then cuttlefish nanoparticles are added, mixed evenly, and cast into a mold to obtain the product.

[0015] The second aspect of the present invention provides a high-strength and high-toughness natural polymer hydrogel wound dressing with excellent photothermal properties prepared by the above method.

[0016] The third aspect of the present invention provides the use of the above-mentioned wound dressing in photothermal antibacterial treatment.

[0017] A fourth aspect of the present invention provides a medical device comprising: the above-mentioned high-strength and high-toughness natural polymer hydrogel wound dressing with excellent photothermal properties.

[0018] Beneficial effects of the present invention

[0019] 1. The present invention first oxidizes SA with NaIO4 to generate OSA with aldehyde groups. Simultaneously, DA is grafted onto the OSA chains via amide bonds between amino groups and aldehyde groups to form an OSA-PDA crosslinked network. Next, PVA and PVP are crosslinked to form a PVA-PVA crosslinked network. Finally, these two networks are combined and melanin NPs are incorporated into the network to produce a PVA-PVP-OSA-PDA-Melanin NPs hydrogel encapsulating melanin NPs. The preparation conditions of this invention are easily achieved, and the raw materials used are all natural, polymer-based materials, making it environmentally friendly and green.

[0020] 2. The present invention first oxidizes SA with NaIO4 to produce a dialdehyde structure. Excess unreacted NaIO4 is then dialyzed to remove the NaIO4, preventing it from oxidizing other monomers and affecting gel properties. DA is then added to graft DA onto OSA, followed by crosslinking in an alkaline environment at pH 11 to produce an OSA-PDA solution. Finally, after mixing with the PVA-PVA solution, melanin NPs are incorporated into the double-crosslinked network, firmly anchoring the melanin NPs within the gel. The order of the reactions described above cannot be altered; otherwise, the dressing with the structure and properties of the present invention will not be obtained. The present invention proceeds in four steps; combining any of the steps will not achieve the superior effects of the present invention. For example, simultaneous oxidation of OSA and PVA with NaIO4 will denature the PVA. Furthermore, the ratio of the different raw materials must be appropriate; otherwise, the dressing with the structure and properties of the present invention will not be obtained.

[0021] 3. The present invention uses PVP and PVA as the main materials of the gel, and then adds DA, SA and Melanin NPs, all of which are natural polymer-based materials; the resulting dressing is green, environmentally friendly, has excellent biocompatibility, good blood compatibility, and is more suitable for human skin.

[0022] 4. The addition of dopamine and melanin NPs to the hydrogel imparts excellent photothermal properties, thereby enhancing its antibacterial properties. The teaphenol groups on the surfaces of DA and melanin NPs possess antioxidant properties, capturing free radicals and enhancing their antioxidant properties. Dopamine and cuttlefish nanoparticles share a similar structure, synergizing with each other in terms of photothermal, antioxidant, antibacterial, compatibility, coagulation, and adhesion properties, while also synergizing with other ingredients to enhance their overall performance.

[0023] 5. The light and heat performance of the dressing of the present invention is 1w / cm -2 After 10 minutes of irradiation with the 808 laser, the temperature rises to about 60°C, which can effectively inhibit the growth of bacteria without damaging skin tissue, thus illustrating the excellent photothermal performance of the present invention.

[0024] 6. The preparation method of the present invention as a whole enables the dressing obtained by the present invention to have excellent mechanical strength, antioxidant and antibacterial properties, good biocompatibility, and excellent photothermal properties. It can effectively heal wounds, ensure stable mechanical strength during the healing period, and will not damage skin tissue. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.

[0026] Figure 1 are SEM images of different gels in Experimental Example 1;

[0027] Figure 2 a is the stress-strain curve of the compression test of different hydrogels in each group; b is the stress-strain curve of the tensile test of different hydrogels in each group;

[0028] Figure 3 a is a graph showing the free radical scavenging rate of different gels tested with ABTS as an indicator in Experiment 3; b is a graph showing the free radical scavenging rate of different gels tested with DPPH as an indicator in Experiment 3; c is a graph showing the free radical scavenging rate of different gels tested with superoxide anion radicals (O2 ·- ) is a graph showing the free radical scavenging rate of different gels tested by an indicator;

[0029] Figure 4 Temperature curves of different gels under 808 laser irradiation in Experimental Example 4. DETAILED DESCRIPTION

[0030] It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0031] Unless otherwise defined, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in accordance with conventional methods in the art or according to product specifications. Similarly, unless otherwise specified, the test methods of the present invention are also tested in accordance with conventional methods in the art or the common methods or standards in the industry. In addition, any methods and materials similar to or equivalent to the described contents can be applied to the inventive method. The preferred embodiments and materials described herein are for demonstration purposes only.

[0032] The first aspect of the present invention provides a method for preparing a high-strength and high-toughness natural polymer hydrogel wound dressing with excellent photothermal properties, comprising:

[0033] The polyvinyl alcohol solution and polyvinyl pyrrolidone are mixed uniformly to obtain a PVA-PVP solution;

[0034] The oxidized sodium alginate and dopamine are mixed uniformly in a solution to obtain an OSA-PDA solution;

[0035] The OSA-PDA solution is added to the PVA-PVP solution to obtain a mixed solution of PVA-PVP-OSA-PDA, and then cuttlefish nanoparticles are added, mixed evenly, and cast into a mold to obtain the product.

[0036] The amount of PVA, PVP, OSA, and PDA will affect the performance of the hydrogel. Therefore, the present invention studies the amount of PVA, PVP, OSA, and PDA. In some embodiments, in the mixed solution of PVA-PVP-OSA-PDA, the mass ratio of PVA, PVP, OSA, and PDA is 8-12:2-3:0.01-1:0.01-0.25, so that the prepared hydrogel has high strength, high toughness, and better photothermal properties.

[0037] The present invention incorporates melanin NPs into a cross-linked network to obtain a PVA-PVP-OSA-PDA-melanin NPs hydrogel encapsulating melanin NPs. In some embodiments, the ratio of the PVA-PVP-OSA-PDA mixed solution to the cuttlefish nanoparticles is 580-585:1 to obtain better performance.

[0038] The particle size of cuttlefish nanoparticles affects the photothermal properties of the hydrogel. Therefore, the present invention studies the particle size range of cuttlefish nanoparticles. In some embodiments, the particle size of the cuttlefish nanoparticles is 100-200 nm, so that the hydrogel has better photothermal properties.

[0039] The present invention does not impose any particular limitation on the preparation method of cuttlefish nanoparticles. In some embodiments, the cuttlefish nanoparticles are separated from the ink sac of cuttlefish by centrifugation at a speed of 18,000 revolutions per minute for 15 minutes.

[0040] Vacuum drying technology has the advantages of low temperature, fast drying speed, and rapid volatilization of water during the drying process. Therefore, in some embodiments, dried Melanin NPs are obtained by drying at 50°C in a vacuum environment.

[0041] In some embodiments, the mass ratio of dopamine to oxidized sodium alginate is 1:1-4, so that DA is grafted onto the OSA chain through amide bonds formed between amino groups and aldehyde groups to form an OSA-PDA cross-linked network.

[0042] In order to uniformly mix OSA and DA, the present invention studies the dosage of OSA and DA. In some embodiments, 2-3 mL of deionized water is required to dissolve OSA and DA, and the stirring time is 20-40 min to fully mix the two.

[0043] The pH value affects the cross-linking effect of dopamine and oxidized sodium alginate. Therefore, in some embodiments, the pH value of the OSA-PDA solution is pH=10-12 to form an OSA-PDA cross-linked network.

[0044] Natural sodium alginate polysaccharide-based hydrogel has the advantages of biocompatibility, non-toxicity, hydrophilicity, hemostasis, low price, easy removal, and similar physicochemical properties to the extracellular matrix. Therefore, in some embodiments, the oxidized sodium alginate is obtained by oxidation reaction of sodium alginate and sodium periodate (NaIO4).

[0045] The amount of SA and NaIO4 used will affect the generation of OSA. Therefore, in some embodiments, the mass ratio of SA to NaIO4 is 1:1-2 to improve the efficiency and yield of the oxidation reaction.

[0046] In order to fully dissolve SA in water, the present invention has studied the dosage of SA and water. In some embodiments, the ratio of the mass of SA to the volume of water is 0.001-0.1 g / mL to improve the dispersion effect of SA in water.

[0047] In order to improve the efficiency and yield of the oxidation reaction, the present invention studies the conditions of the oxidation reaction. In some embodiments, the temperature during the oxidation reaction is room temperature, and the reaction is carried out for 5-7 hours under light-proof and stirring conditions to improve the preparation efficiency and quality of OSA.

[0048] In some embodiments, the ratio of the mass of SA to the volume of EG is 0.1-1.5 g / mL. The present invention uses ethylene glycol to terminate the reaction to ensure the purity and effectiveness of the reaction.

[0049] In order to ensure the effect of ethylene glycol on the termination reaction, the present invention studies the reaction conditions of ethylene glycol. In some embodiments, after adding EG, the reaction is stirred at room temperature for 0.5-2 hours to effectively terminate the reaction.

[0050] The present invention uses dialysis to purify OSA and studies the dialysis conditions. In some embodiments, a dialysis bag with a molecular weight cutoff (Mw) of 8000 Da is used for dialysis. The dialysis is performed for 2-4 days, and the deionized water needs to be replaced every 7-9 hours during the dialysis process to obtain OSA with higher purity.

[0051] Polyvinyl alcohol (PVA) is highly biocompatible and provides the primary crosslinking network in hydrogels. Polyvinyl alcohol-based hydrogels are widely used in biomedicine due to their simple structure and excellent physical and chemical properties. Polyvinyl pyrrolidone (PVP) is a proven effective skin regeneration and wound dressing material. Therefore, in some embodiments, the mass ratio of the PVA solution to PVP is 1:5-10.

[0052] In some embodiments, during the dissolution process, PVA is first added to 3-7 mL of water to fully swell, and then the temperature is raised to 85-95° C. to fully dissolve it.

[0053] The present invention also studies the mixing temperature of PVA and PVP. In some embodiments, PVP is added to the solution after the temperature is cooled to 20-25° C. and the mixture is mixed evenly.

[0054] Casting molding has the advantages of simple production process and relatively easy mold making. Therefore, in some embodiments, the specific steps of the casting molding include: cooling the mixed solution into gel, and thawing to obtain.

[0055] The cooling temperature for gelling affects the final properties of the gel material. Therefore, the present invention studies the cooling temperature for gelling. In some embodiments, the cooling temperature for gelling is -10-30°C and the time required is 22-26 hours to improve the properties of the gel material.

[0056] The number of freeze / thaw cycles, temperature, and time can affect the mechanical properties of the hydrogel. Therefore, in some embodiments, the hydrogel is thawed at room temperature for 22-26 hours to provide the hydrogel with better mechanical properties.

[0057] More specifically, they include:

[0058] (1) Melanin nanoparticles were separated from the ink sac of cuttlefish by centrifugation. After multiple washings, a pure dispersion of melanin nanoparticles was obtained. Dry melanin nanoparticles (Melanin NPs) were obtained by vacuum drying.

[0059] (2) Sodium alginate (SA) is dissolved in water, followed by the addition of sodium periodate (NaIO4) for oxidation, followed by the addition of ethylene glycol (EG) to terminate the reaction. The product is dialyzed and freeze-dried to obtain oxidized sodium alginate (OSA).

[0060] (3) Dissolve polyvinyl alcohol (PVA) in water, then add polyvinyl pyrrolidone (PVP) and mix well. Then dissolve oxidized sodium alginate (OSA) and dopamine (DA) in water, stir for 30 minutes, adjust the pH, and continue stirring for 30 minutes.

[0061] (4) The above OSA-PDA solution was added to the PVA-PVP solution, and Melanin NPs were added and mixed evenly, and then cast into a mold to prepare PVA-PVP-OSA-PDA-Melanin NPs hydrogel (POM hydrogel).

[0062] The present invention will be further described in detail below with reference to specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0063] In the examples, cuttlefish nanoparticles were prepared according to the method described in the document “Superior Performance of PolyurethaneBased on Natural Melanin Nanoparticles, Biomacromolecules 2016, 17, 3782-3789”.

[0064] Example 1:

[0065] A method for preparing a high-strength and high-toughness natural polymer hydrogel wound dressing with excellent photothermal properties comprises the following steps:

[0066] S1. Melanin NPs were isolated from the cuttlefish ink sac by centrifugation at 18,000 revolutions per minute for 15 minutes. After multiple washes, a pure melanin NP dispersion was obtained. Dry melanin NPs were obtained by vacuum drying (50°C).

[0067] S2. Dissolve 1 g of SA in 100 ml of water, add 1.5 g of NaIO4, and stir at room temperature in the dark for 6 h. Then add 2 mL of EG and stir at room temperature for 1 h. The product is placed in a dialysis bag (Mw = 8000 Da) and dialyzed for 3 days, changing the water every 8 h. The product is then freeze-dried to obtain OSA.

[0068] S3. PVA was added to 15 mL of water to fully swell, then heated to 90°C to dissolve. After cooling to room temperature, PVP was added and mixed thoroughly. The weight percentages of PVA and PVP were 10 wt% and 2.5%, respectively. OSA and DA were then dissolved in 2.25 mL of water to prepare solutions of 1 wt% and 0.25 wt%, respectively. The solution was stirred for 30 minutes, and the pH of the solution was adjusted to 11. Stirring was continued for 30 minutes.

[0069] S4. Add the OSA-PDA solution to the PVA-PVP solution and 34.4 mg of melanin NPs. Mix thoroughly and cast into a mold. Finally, cool at -20°C for 24 hours and thaw at room temperature for 24 hours to prepare the PVA-PVP-OSA-PDA-Melanin NPs hydrogel (POM 2).

[0070] Example 2

[0071] A high-strength, high-toughness natural polymer hydrogel wound dressing with excellent photothermal properties was prepared as described in Example 1, except that 86.25 μg of myrtle ketone (T90) was additionally added in step S4. All other steps and conditions were the same as in Example 1. The resulting hydrogel was designated PVA-PVP-OSA-PDA-T90 hydrogel (POM 2T).

[0072] Comparative Example 1

[0073] A method for preparing a hydrogel wound dressing comprises the following steps:

[0074] S1. Dissolve 1 g of SA in 100 ml of water, add 1.5 g of NaIO4, and stir at room temperature in the dark for 6 h. Then add 2 mL of EG and stir at room temperature for 1 h. Place the product in a dialysis bag (Mw = 8000 Da) and dialyze for 3 days, changing the water every 8 h. Then, freeze-dry to obtain OSA.

[0075] S2. Add a certain amount of PVA to 15 mL of water to fully swell it. Then, heat it to 90°C to dissolve it. After cooling to room temperature, add PVP and mix thoroughly. The weight percentages of PVA and PVP are 10 wt% and 2.5%, respectively. Then, dissolve OSA and DA in 2.25 mL of water to prepare solutions of 1 wt% and 0.25 wt%, respectively. Stir for 30 minutes, then adjust the solution to pH 11 and continue stirring for 30 minutes.

[0076] S3. Add the above OSA-PDA solution to the PVA-PVP solution, mix well, and cast into a mold. Finally, cool at -20°C for 24 hours and thaw at room temperature for 24 hours to prepare PVA-PVP-OSA-PDA hydrogel (POM 1).

[0077] Comparative Example 2

[0078] A method for preparing a hydrogel wound dressing comprises the following steps:

[0079] S1. Add a certain amount of PVA to 15 mL of water to fully swell it, then heat it to 90°C to dissolve it, cool it down to room temperature, add PVP and mix evenly. The weight percentages of PVA and PVP are 10 wt% and 2.5% respectively.

[0080] S2. The above PVA-PVP solution was mixed evenly and cast into a mold, and finally cooled at -20°C for 24 hours and thawed at room temperature for 24 hours to prepare PVA-PVP hydrogel (POM 0).

[0081] Test Example 1

[0082] SEM characterization

[0083] Test samples: hydrogels prepared in Example 1 and Comparative Examples 1-2.

[0084] Test method: Scanning electron microscopy (SEM) was used to observe the morphology of three groups of hydrogels: POM 0, POM 1, and POM 2.

[0085] Depend on Figure 1 The SEM images show that the network structure of the POM 0 hydrogel has larger pores than those of POM 1 and POM 2. This is because the POM 0 hydrogel only has two components, PVA and PVP, with a low degree of cross-linking, while the POM 2 hydrogel contains five components—PVA, PVP, OSA, PDA, and cuttlefish nanoparticles—with a higher degree of cross-linking, resulting in a denser hydrogel network and lower porosity. This unique structure not only effectively absorbs exudate from the wound surface but also provides an ideal microenvironment for cell growth.

[0086] Test Example 2

[0087] Compression and tension properties

[0088] Test samples: hydrogels prepared in Example 1 and Comparative Examples 1-2.

[0089] Testing Methods: Tensile and compression tests were conducted on each hydrogel using a universal materials testing machine. For the tensile test, rectangular specimens with a width of 10 mm, a length of 80 mm, and a thickness of 2.5 mm were prepared. The tensile rate was set at 50 mm / min. For the compression test, the hydrogels were formed into cylinders with a height of 20 mm and a diameter of 25 mm. The compression rate was set at 5 mm / min, and the strain range was 0-80%.

[0090] like Figure 2 In the compression test, all hydrogels withstood 83% compression deformation without breaking. Among them, the compressive stresses of POM 0, POM 1 and POM 2 were 0.047, 0.034 and 0.176 MPa, respectively. Due to the introduction of double network and Melanin NPs, the tensile properties of POM 2 hydrogel are significantly better than those of POM 0 and POM 1. Figure 2 In middle b, the tensile stress of POM 2 is 1.08 MPa, while the tensile stresses of POM 0 and POM 1 are 0.491 MPa and 0.108 MPa, respectively. These results demonstrate that the MOP hydrogel with double networks and Melanin NPs has strong mechanical properties sufficient to meet the needs of hydrogel dressings in daily life.

[0091] Test Example 3

[0092] In vitro antioxidant capacity test

[0093] Test samples: hydrogels prepared in Examples 1-2 and Comparative Examples 1-2.

[0094] Test method: The antioxidant capacity of Melanin NPs and hydrogels was determined by 2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) free radical scavenging method to detect their ability to capture free radicals. After mixing 7.4mmol / L ABTS and 2.6mmol / L potassium persulfate, incubate in the dark for 12h, and then dilute 40 times with PBS to obtain the ABTS free radical scavenging working solution. The sample was immersed in the ABTS working solution in a dark environment at 37°C for 30min. The UV spectrum of the mixed solution was then measured and the absorbance at 734nm was read. The percentage calculation formula of ABTS scavenging ability is:

[0095] Clearance rate = (1-A / A i )×100%

[0096] Among them A i is the initial absorbance of ABTS solution, A t It is the absorbance of ABTS solution after mixing with the sample for a certain period of time. Figure 3 a)

[0097] The antioxidant capacity of melanin NPs, hydrogels, and T90 was determined using the 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH) free radical scavenging assay. A 0.1 mM DPPH / ethanol solution was prepared. The samples were then immersed in the DPPH solution at 37°C in the dark for 30 minutes. The UV spectrum of the mixture was then measured, and the absorbance at 517 nm was read. The DPPH scavenging capacity was calculated as follows:

[0098] Clearance rate = (1-A1 / A0) × 100%

[0099] Where A0 is the initial absorbance of DPPH solution, and A1 is the absorbance of DPPH solution after mixing with the sample for a certain period of time. Figure 3 b)

[0100] The superoxide anion free radical scavenging ability test kit was used to test the O2 ·- First, prepare the test solution according to the kit instructions. Then, mix the sample with the test solution and incubate for 30 minutes. Then, measure the UV spectrum of the mixture by UV spectrophotometer and read the absorbance at 530nm. The O2 removal efficiency of the sample was calculated according to the formula ·- The cleaning ability

[0101] Clearance rate = (1-A H / A C )×100%

[0102] Among them, A C is the initial absorbance of the detection solution; A H It is the absorbance of the test solution after mixing with the sample at a certain time. Figure 3 c)

[0103] Depend on Figure 3 As can be seen in Figures a, b, and c, the antioxidant capacity of the gel gradually increased with the cumulative addition of OSA-PDA, Melanin NPs, and T90, and the free radical scavenging capacity was strongest when OSA-PDA, Melanin NPs, and T90 were all present. PVA-PVP alone had the lowest antioxidant capacity.

[0104] Test Example 4

[0105] Photothermal capacity test

[0106] Test sample: hydrogel prepared in Example 1 and Comparative Examples 1-2

[0107] Test method: Take the same volume of hydrogel and put it in a centrifuge tube. Insert the thermocouple thermometer probe into the gel and -2 ) irradiation, record the change of gel temperature every 1 minute for a total of 10 minutes, and make a temperature rise curve of different materials over time ( Figure 4 ).

[0108] Depend on Figure 4 It can be seen that at 808nm (1W / cm 2 After 10 minutes of irradiation, the photothermal temperatures of POM 1 and POM 2 reached 48°C and 63°C, respectively. However, compared to POM 0, the photothermal temperature of POM 0 only reached 20.7°C, indicating that the addition of melanin NPs and OSA-PDA to the POM hydrogel significantly improved its photothermal performance. Based on these photothermal temperatures, POM 2 was selected as the final formulation because a photothermal temperature of 60°C not only effectively kills bacteria but also does not burn the skin.

[0109] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A method for preparing a high-strength and high-toughness natural polymer hydrogel wound dressing with excellent photothermal properties, characterized in that: include: The polyvinyl alcohol solution and polyvinyl pyrrolidone are mixed uniformly to obtain a PVA-PVP solution; The oxidized sodium alginate and dopamine are mixed uniformly in a solution to obtain an OSA-PDA solution; The OSA-PDA solution is added to the PVA-PVP solution to obtain a mixed solution of PVA-PVP-OSA-PDA, and then cuttlefish nanoparticles are added, mixed evenly, and cast into a mold to obtain the product.

2. The method for preparing a high-strength and high-toughness natural polymer hydrogel wound dressing with excellent photothermal performance according to claim 1, characterized in that: In the mixed solution of PVA-PVP-OSA-PDA, the mass ratio of PVA, PVP, OSA, and PDA is 8-12:2-3:0.01-1:0.01-0.25; Alternatively, the ratio of the PVA-PVP-OSA-PDA mixed solution to the cuttlefish nanoparticles is 580-585:

1.

3. The method for preparing a high-strength and high-toughness natural polymer hydrogel wound dressing with excellent photothermal performance according to claim 1, characterized in that: The particle size of the cuttlefish nanoparticles is 100-200 nm.

4. The method for preparing a high-strength and high-toughness natural polymer hydrogel wound dressing with excellent photothermal performance according to claim 1, characterized in that: The mass ratio of dopamine to oxidized sodium alginate is 1:1-4; Alternatively, the oxidized sodium alginate is obtained by oxidation reaction of sodium alginate and sodium periodate (NaIO4).

5. The method for preparing a high-strength and high-toughness natural polymer hydrogel wound dressing with excellent photothermal performance according to claim 1, characterized in that: The mass ratio of the polyvinyl alcohol solution to polyvinyl pyrrolidone is 1:5-10.

6. The method for preparing a high-strength and high-toughness natural polymer hydrogel wound dressing with excellent photothermal performance according to claim 1, characterized in that: The specific steps of the casting molding include: cooling the mixed solution into gel, and thawing to obtain the product.

7. The method for preparing a high-strength and high-toughness natural polymer hydrogel wound dressing with excellent photothermal performance according to claim 6, characterized in that: The cooling temperature for gelling is -10-30°C and the time required is 22-26 hours; Alternatively, thaw at room temperature for 22-26 hours.

8. A high-strength and high-toughness natural polymer hydrogel wound dressing with excellent photothermal properties prepared by the method according to any one of claims 1 to 7.

9. Use of the wound dressing according to claim 8 in photothermal antibacterial treatment.

10. A medical device, characterized in that: include: The high-strength and high-toughness natural polymer hydrogel wound dressing with excellent photothermal properties as described in claim 8.